2012
DOI: 10.1177/0888406412453930
|View full text |Cite
|
Sign up to set email alerts
|

Building School and Teacher Capacity to Eliminate the School-to-Prison Pipeline

Abstract: The school-to-prison pipeline (STPP)—disproportionately impacting students of color— involves a set of interactions between and among children, youth, their families, school personnel, other service providers, and gatekeepers to such outcomes as incarceration or college. Educators can, through their interactions with and expectations for students, contribute significantly to negative outcomes or lead the charge toward more positive outcomes. In this article, the authors first examine four factors that amplify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Creating a culture of health in school depends on integrating other interlocking systems to include the family and community. Increasing dialogue between school personnel and parents to talk about issues of race and racism cultivates a culture of respect and trust . A vital aspect of such change efforts includes sharing evidence on school suspension to guide discussions on reducing bias and improving decision‐making.…”
Section: Implications For School Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Creating a culture of health in school depends on integrating other interlocking systems to include the family and community. Increasing dialogue between school personnel and parents to talk about issues of race and racism cultivates a culture of respect and trust . A vital aspect of such change efforts includes sharing evidence on school suspension to guide discussions on reducing bias and improving decision‐making.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…The Supporting and Responding to Behavior published by the US Office of Special Education Programs proposes positive behavioral interventions that emphasize fair consequences, de‐escalation, alternative learning opportunities where both teachers and students learn how to model other ways to deal with conflict can begin to address the root causes of racial inequality in school suspension . A review of school practices that lead to declines in school suspension found students were less like to engage in truant and delinquent behavior when they perceived teachers as fair and felt valued . Working with school professionals in addressing their biases to respond to culturally and racially diverse youth in valuable ways potentially improve student‐teacher relationships and increase school connectedness .…”
Section: Implications For School Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Students want to attend safe schools where they can learn; families want their children to attend safe and productive schools; teachers, staff, and administrators want to work in safe environments that minimize distractions; and public policy mandates safety and achievement. The frequent response to the lack of school safety and the presence of student disorder is control-oriented approaches that include surveillance through technology, punishment, and exclusionary discipline.…”
Section: The Problemmentioning
confidence: 99%